Geração de dados espaciais vagos baseada em modelos exatos - Proença, Fernando Roberto (Universidade Federal de São Carlos, 2013)
Geographic information systems with the aid of spatial databases store and manage crisp spatial data (or exact spatial data), whose shapes (boundaries) are well defined and have a precise location in space. However, several spatial data do not have precisely known boundaries or have an uncertain location in space, which are called vague spatial data. The boundaries of a given vague spatial data may shrink or extend, therefore, may have a minimum and maximum extension. Clouds of pollution, deforestation, fire outbreaks, route of an airplane, habitats of plants and animals are examples of vague spatial data. In the literature, there are currently vague spatial data models, such as Egg-Yolk, QMM and VASA. However, according to our knowledge, they focus only on the formal aspect of the model definition. Thus, real or synthetic vague spatial data is not available for use. The main objective of this master thesis is the development of algorithms for the generation of synthetic vague spatial data based on the crisp models of spatial data vague Egg-Yolk, QMM and VASA. It was also implemented a tool, called VagueDataGeneration, to assist in the process of generation such data. For both the algorithms and the tool, the user is able to set the properties related to the data type of model, such as size, shape, volume, complexity, location and spatial distribution. By using the proposed algorithms and the VagueDataGeneration tool, researchers can generate large samples of vague spatial data, enabling new research, such as testing indexes for vague spatial data or evaluating query processing over data warehouses that store vague spatial data. The validation of the vague spatial data generation was conducted using a case study with data from vague rural phenomena.
Keywords: Banco de dados; Sistema de informação; Sistemas de informação geográfica; Java (Linguagem de programação de computador); Modelos exatos de dados espaciais vagos; Geração dedados espaciaisvagos; Dados sintéticos; Egg-Yolk; QMM; VASA; Vague spatial data crisp models; Vague spatial objects; Vague spatial data generation; Synthetic data; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO